2019
DOI: 10.1111/oik.06138
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between functionally diverse fungal mutualists inconsistently affect plant performance and competition

Abstract: Plants form mutualistic relationship with a variety of belowground fungal species. Such a mutualistic relationship can enhance plant growth and resistance to pathogens. Yet, we know little about how interactions between functionally diverse groups of fungal mutualists affect plant performance and competition. We experimentally determined the effects of interaction between two functional groups of belowground fungi that form mutualistic relationship with plants, arbuscular mycorrhizal (AM) fungi and Trichoderma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 53 publications
(94 reference statements)
0
7
0
Order By: Relevance
“…The AMF mediated plant community dynamics are context-dependent, as soil nutrient availabilities and C allocation from plants to extraradical hyphae determine the relationships between plants and symbiotic partners (Walder & van der Heijden, 2015). Many previous studies have found that mycorrhizal fungi mediate competitive abilities between plant species and alter plant community structure under different nutrient conditions (Lin et al, 2015;Scheublin et al, 2007;Thakur et al, 2019;Wagg et al, 2011). Under low nutrient conditions, plants with high mycorrhizal responses can be facilitated by AMF to gain a competitive advantage.…”
Section: Mr Is the Proximate Driver Of Plant Community Changesmentioning
confidence: 99%
“…The AMF mediated plant community dynamics are context-dependent, as soil nutrient availabilities and C allocation from plants to extraradical hyphae determine the relationships between plants and symbiotic partners (Walder & van der Heijden, 2015). Many previous studies have found that mycorrhizal fungi mediate competitive abilities between plant species and alter plant community structure under different nutrient conditions (Lin et al, 2015;Scheublin et al, 2007;Thakur et al, 2019;Wagg et al, 2011). Under low nutrient conditions, plants with high mycorrhizal responses can be facilitated by AMF to gain a competitive advantage.…”
Section: Mr Is the Proximate Driver Of Plant Community Changesmentioning
confidence: 99%
“…Ten days after germination, the seedlings were transplanted into 400 mL pots containing a sterile sand/vermiculite mixture (1:1, v/v). Inoculation with R. irregularis was performed by mixing the R. irregularis inoculum with the sand/vermiculite mixture at 10% (v/v) before transplanting [95]. Inoculation with T. harzianum was achieved by mixing the T. harzianum inoculum with the substrate to achieve a final density of 1 × 10 6 conidia g −1 before transplanting [95].…”
Section: Plant Growth Conditions and Fungal Inoculationmentioning
confidence: 99%
“…Inoculation with R. irregularis was performed by mixing the R. irregularis inoculum with the sand/vermiculite mixture at 10% (v/v) before transplanting [95]. Inoculation with T. harzianum was achieved by mixing the T. harzianum inoculum with the substrate to achieve a final density of 1 × 10 6 conidia g −1 before transplanting [95]. The plants were then placed in a completely randomized design in controlled climate chambers at 16 h/8 h day/night cycle, 65-70% RH.…”
Section: Plant Growth Conditions and Fungal Inoculationmentioning
confidence: 99%
“…In particular, the Mediterranean region could be especially vulnerable, with the extinction of more than 2000 plant species [67] and negative consequences on the structure, dynamics and functioning of forests [68,69]. Therefore, populations will have to adapt to and compete in new environmental conditions, and the response of the fungal communities will be part of that ecological competition [70,71], producing changes in the composition of the species in the ectomycorrhizal communities [8,72]. For this reason, taxa collected in the summer season, although not important from a quantitative point of view, should be of great importance as they are able to fructify in the most adverse weather conditions, and potentially, they are the best adapted to some conditions that could be extended throughout the year.…”
Section: Climatic and Meteorological Factorsmentioning
confidence: 99%